Tracking timescales of magma reservoir recharge through caldera cycles at Santorini (Greece). Emphasis on an explosive eruption of Kameni Volcano - Polo-Sánchez, Antonio; Flaherty, Taya; Hervé, Garance; Druitt, Tim; Fabbro, Gareth N.; Nomikou, Paraskevi; Balcone-Boissard, Helène (Frontiers in Earth Science, 2023)
Pre-eruptive processes and their timescales are critical information for risk management at explosive volcanoes, and Santorini caldera (Greece) provides an excellent context in which to approach this subject. We ask two questions. First, are pre-eruptive processes the same for small and big eruptions? To investigate, we performed a multi-mineral diffusion timescale study of a small explosive eruption of Kameni Volcano and compared the results with those published for larger caldera-forming eruptions at Santorini. The Kameni dacite resembles products of larger eruptions in being crystal-poor, containing plagioclase with antecrystic cores and autocrystic rims, bearing orthopyroxene with sector zoning and phantom skeletal morphologies, and showing evidence for mixing of different silicic magmas prior to eruption. Diffusion timescales from Mg-Fe profiles in orthopyroxene and clinopyroxene phenocrysts are <1–23 years, and Mg diffusion modelling in plagioclase gives <10 years. Our physical model for the Kameni eruption is similar to those proposed for larger eruptions, where silicic melt produced in gabbroic to dioritic lower to middle crustal mush bodies is transferred (along with entrained mafic magma) to an upper crustal reservoir. Crystals grow in the hydrous silicic melts due to decompression, cooling, and magma mixing during ascent and injection into upper crust. We propose that large eruptions are preceded by similar processes as small ones, but on a larger scale. Our second question: do diffusion timescales relate to eruptive volume or position in a caldera cycle? For this, we obtained orthopyroxene Mg-Fe diffusion timescales for three additional eruptions, growing our orthopyroxene timescale database to seven eruptions of different sizes and cycle timings. No clear relationship exists between diffusion timescale and volume; however, timescales are systematically shorter (<0.01–10 years) early in a cycle and longer (1–5,000 years) late in a cycle. Thermal maturation and H2O-flushing of the crustal magma reservoir through the caldera cycle could explain this, as the reservoir would change from a rigid to more mushy state as the cycle progresses. This would change the mechanical response to melt input and allow accumulation of progressively larger melt layers in the upper crust, resulting in increasing crystal residence times.